Oxygenated edge plane sites slow the electron transfer of the ferro-/ferricyanide redox couple at graphite electrodes. - Ji, X; Banks, C; Crossley, A; Compton, R (2006)
The electron transfer kinetics of ferrocyanide, potassium hexachloroiridate(III), hexaammineruthenium(III) chloride, and N,N,N',N'-tetramethyl-p-phenylenediamine (TMPD) have been examined at basal plane and edge plane pyrolytic graphite electrodes which have been allowed to oxidise in air for various periods of time. It is demonstrated via voltammetric and X-ray photoelectron spectroscopy (XPS) analysis that oxygenated species formed at edge plane sites/defects decrease the electron transfer kinetics of ferrocyanide but that the rates for potassium hexachloroiridate(III), hexaammineruthenium(III) chloride and TMPD are insensitive to the oxygenated species. The behaviour of the ferro-/ferricyanide couple contrasts with that seen on single-walled carbon nanotubes where oxygenation of the tube ends is known to speed up the electron transfer kinetics (A. Chou, T. Bocking, N. K. Singh, J. J. Gooding, Chem. Commun. 2005, 842); the possible reasons for this contrasting behaviour are discussed.